How to: quaking aspen - Colorado State Forest Service, author (Colorado State University. Libraries, 2012)
The brochure offers information on the management and treatment of burned quaking aspen trees on private property.
Keywords: fire damage; management decisions; fire injury; survivability; quaking aspen